(untitled) (World Bulletin of Management and Law, 2022)
Since 2003, Iraq has been at the bottom of The Corruption Perceptions Index (CPI) of Transparency International and has become one of the most corrupt countries in the world. It is also expected to remain so for a longer period, which is what preoccupies the Iraqi society and the international community given the decline of development and investment opportunities and the undermining of the legitimacy of the achievement of the existing political system. Iraq did not witness, even during the time of the previous regime, i.e. before 9/4/2003, the spread of corruption in all its forms in this notorious scale. The growing scale of corruption and the interconnectedness of its mechanisms and circles threaten the stability of Iraq and hinder the building of political, administrative, and social institutions, and the development economic process. This type of corruption is the most serious and it destroys the development process as it drains resources and undermines the infrastructure that forms the cornerstone of the development process. It threatens the sovereignty of the state because of large debts from which it will suffer as it cannot generate sufficient revenues to meet those debts and achieve a level of growth acceptable to its existence. It is important to note that the issue of corruption, particularly administrative corruption, is not limited to the detrimental consequences it has on a single sector of society. Rather, its effects extend to all members and sectors of society. It directly affects the state’s economy by impeding the process of economic growth. Corruption also leads to the imbalance in the social structure of society and results in familiarizing individuals with practices that are rejected by every society that seeks to preserve the values and principles on which it was built. In addition, it has an effect on politics, when structures and organizations based on bribery and capital control come to light, upsetting the established order of the political game. Many researchers and those who are interested have paid attention to the issue of corruption. There was agreement that an institutional framework needed to be developed and established in order to tackle this phenomena through concrete steps, in all its forms and manifestations and in all spheres of life, to accelerate the process of economic development.